INTEGRASI NILAI-NILAI PANCASILA PADA PRAKTIK PEMBELAJARAN KEWARGANEGARAAN DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW DAN BIBLIOMETRIC ANALYSIS - Naning Tyas Ayu Hera Warsito; Intan Sari Rufiana; Radeni Sukma Indra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines contemporary practices of citizenship education grounded in Pancasila values in Indonesian primary schools through a combined Systematic Literature Review and bibliometric analysis. Rapid sociotechnical changes in the 2020s have intensified the need for pedagogical approaches that not only build civic knowledge but also cultivate value-oriented behavior aligned with the Pancasila profile of learners. The review synthesizes empirical evidence published between 2020 and 2025 to identify effective instructional strategies and the mechanisms through which cognitive, affective, and behavioral dimensions of value internalization are fostered. Using PRISMA-guided procedures, 18 eligible articles were systematically analyzed, complemented by bibliometric mapping of publication trends, co-authorship networks, and keyword co-occurrences. The findings reveal growing scholarly attention to project-based learning, service-based activities, role-playing, and culturally embedded school programs as means to strengthen moral reasoning, cooperation, and democratic dispositions among young learners. Nevertheless, considerable variation remains in pedagogical quality, research rigor, and assessment instruments, with many studies relying on small samples and non-standardized measures. Bibliometric patterns indicate fragmented research clusters and limited interdisciplinary collaboration, highlighting conceptual gaps in operationalizing Pancasila-based citizenship competencies. The study concludes that integrated, experiential, and contextually grounded learning designs hold strong potential to reinforce Pancasila values, yet require more robust empirical validation. The combined SLR–bibliometric approach provides a comprehensive evidence base and research roadmap for policymakers, educators, and future researchers seeking to advance value-based civic education at the primary level.